Unraveling the individual and interactive effects of climate and competition on branch growth dynamics in Pinus koraiensis in Northeast China - Xuehan Zhao; Zheng Miao; Zheng Miao; Fengri Li; Fengri Li; Yuanshuo Hao; Yuanshuo Hao; Yumeng Jiang; Lihu Dong; Lihu Dong (Frontiers in Plant Science)
IntroductionThe quantitative modeling of dynamic branch growth in Korean pine (Pinus koraiensis) and the analysis of the factors influencing branch growth are essential prerequisites for making scientifically sound management decisions in Korean pine plantations. To date, the effects of competition, climate and their interactions on branch growth have been insufficiently investigated. Additionally, limited knowledge exists regarding whether these impacts vary depending on the social status of trees. In the face of the current challenges posed by climate change, accurate information to inform forest management and policy-making is urgently needed.MethodsWe collected 745 branches from 54 sampled trees of Korean pine and, we employed a mixed-effects model to assess the effects of tree variables, competition, climate, and their interactions on branch growth. Furthermore, we simulated branch growth under different combinations of competition and climatic conditions to provide practical and targeted recommendations for Korean pine plantation management.ResultsOur results demonstrate that (1) in addition to branch age, size, and tree height growth, competition, climate, and their interactions significantly improved the branch growth model, with the effects of interactions surpassing the individual effects of climate, which highlights the importance of considering interactive effects; (2) the effects of climate and competition varied depending on the social status of the trees, with dominant and intermediate individuals showing greater sensitivity to competition and climate than suppressed individuals, suggesting that, for future research in this direction, prioritizing sampling of dominant and intermediate individuals would be a cost-effective approach; and (3) owing to the presence of interactions, the influence of climate on branch growth was modulated by competition, suggesting that adjusting competition levels in response to climate stress could lead to desirable branch growth outcomes.DiscussionOur study underscores the importance of understanding the different sources of variation in branch growth is crucial for advancing our understanding of tree growth and crown dynamics, as well as for formulating sustainable management policies amidst the uncertainties of climate change.